InfraCo Asia: Bringing wireless broadband to Indonesia’s rural regions - NAQVI, Ijlal (Institutional Knowledge at Singapore Management University, 2021)
In November 2020, infrastructure investment and development company InfraCo Asia Pte Ltd, investment management firm Gemcorp Capital, and Finnish development financier Finnfund’s OP Finnfund Global Impact Fund I jointly financed the Indonesia Rural Wireless Broadband (IRWB) project through a senior debt facility of US$75 million. The IRWB project is expected to expand the fixed wireless broadband network of borrower Net1 Indonesia by installing 1,500 base transceiver stations (BTS) across the country, up almost five times from the existing figure of 357 BTS before the expansion commenced. The project would cover several provinces, including nine that are considered the least developed in Indonesia. It is estimated that 300,000 households, particularly those that fell between the fourth and last (i.e., poorest) quintile of the population, would benefit from the project. In deciding whether to proceed with financing the project, InfraCo Asia, which is funded by the foreign ministries of the UK, the Netherlands, Switzerland, and Australia, had to take into consideration several factors: risk management, commercial viability, technology, due diligence, business model, and development impact (DI). The case examines how InfraCo Asia ensured that the decision to finance the IRWB project is a well-considered one, such that the project has a fair chance of being commercially viable while also achieving considerable DI. The learning objectives for the case discussion are: understand the relationship among DI, commercial viability, and additionality, and how they affect the decision on financing an infrastructural project; recognise the salient similarities and differences between the private-sector-fronted development financing model and the typical PPP; and appreciate that DI is a wide-ranging term that can affect various aspects of the lives of the disadvantaged beyond top-of-mind concerns like poverty.